Radiochemotherapy for salivary gland adenoid cystic carcinoma: survival assessment through a retrospective study exploiting real-world data extracted from data warehouse - S. Cavalieri; B. Lombardi Stocchetti; N. Crippa; C. Silvestri; C. Villa; F. Ghelardi; P. Baili; S. Bonfarnuzzo; I. Cavallo; N.A. Iacovelli; M. Franceschini; A.R. Filippi; et al. (ESMO Real World Data and Digital Oncology, 2025)
Background and purpose: Adenoid cystic carcinoma (ACC) is a rare salivary gland malignancy often characterized by an indolent course but significant risk of distant metastasis. The role of concurrent chemoradiotherapy (CRT) in improving oncologic outcomes remains controversial. This study aimed to assess the potential benefits of CRT compared with exclusive radiotherapy (RT) in ACC patients treated with curative intent. Materials and methods: A retrospective cohort study was conducted using real-world data from a tertiary cancer center. Patients with head and neck ACC treated with curative RT between 2007 and 2022 were analyzed. Outcomes were evaluated using Kaplan–Meier and Cox regression analyses. Propensity score matching (PSM) was employed to control for confounding factors. The primary survival outcomes were distant metastasis-free survival (DMFS) and distant metastasis-free interval (DMFI). Results: A total of 178 patients were included (89% receiving surgery), of whom 24 received CRT. Median follow-up was 85.2 months. In the unmatched cohort, CRT showed a trend toward improved DMFS (median 101.38 months versus 50.16 months, P = 0.052) and DMFI (101.38 months versus 53.25 months, P = 0.071). PSM analysis (n = 40) demonstrated statistically significant improvement in DMFI for CRT (median 101.38 months versus 39.8 months, P = 0.032; hazard ratio for distant metastasis 0.43, P = 0.037). No significant differences were observed in overall survival or locoregional control. Conclusions: CRT may delay the onset of distant metastasis and extend DMFI in ACC patients, particularly younger and fit individuals. While overall survival benefits were not observed, these findings support CRT consideration in selected patients. Further prospective studies are warranted to confirm these results.